Results from Portugal's 2022 report card on physical activity for children and youth - Pizarro, Andreia (2023)
Background/Objectives: The purpose of this study is to update results of Portuguese's Report Card on Physical activity (PA) for Children and Adolescents. Methods: The grades were assigned by results derived from the PA and Fitness in Portugal 2021 Portuguese Report Card and corresponds to the third report for the Portuguese children and adolescents. It includes indicators of PA and sedentary behavior (SB) that are common to the GLOBAL matrix 4.0: Overall Physical Activity, Organized Sport and Physical Activity, Active Play, Active Transportation, Sedentary Behaviors, Family and Peers, School, Community and the Environment, Government and Physical Fitness. The search focused on published national evidence/data sources (academia, NGO, governmental) from end 2018 onwards excluding data obtained during the covid-19 pandemic. Results: The grades were assigned as follows: Overall PA (D ), Organized Sport Participation (C ), Active Play (Dþ), Active Transportation (D ), Sedentary behaviors (Cþ), Physical Fitness (C), Family and Peers (B), School (A), Community and Environment (B), and Government (B). Conclusion: In line with previous Portuguese Report Cards, a large proportion of Portuguese children and adolescents are not sufficiently active nor fit enough setting urgency for effective strategies. Particular attention should be given to Active play, Active transport and Organized Sports Participation has their grades have decreased. Some actions in selected indicators as Governmental and policy seems promising however results weren't seen yet. Despite the strong support of schools with mandatory curricula in PE no correspondent change is observed in fitness or PA, so more research is needed to find why.